Relationship between postural abnormalities and functional movement assessments in table tennis players - Pooryamanesh, L.; Zarei, M.; Ansari, M. A.; Dana, S. (Proceedings Book of The 16th ITTF Sports Science Congress Budapest (HUN), April 19th - 20th, 2019, 2020)
Table tennis is one of the popular sports that many people playing this sport. During matches and exercises, especially in young athletes, the body adapts to postural deviations that are suitable for table tennis and affect movement efficiency. Aim and theoretical framework: Athletes need to spend a lot of time in the dominant physical habit of the sport, so the posture in athletes may be affected and lead to changes in functional movements. Therefore, our aim in this study is to determine the Relationship between postural abnormalities and Functional Movement Assessments in table tennis players. Method: 51 male table tennis players with age (13.68±2.83) were selected randomly. For evaluation of movement efficiency, three functional movements including double limb squat, double limb squat with heel lift, and single limb squat were conducted for assessing movement dysfunctions and scored using Fusionetics algorithms. For assessing postural abnormalities, New York test and plumb line were used. Results: The results shown that table tennis players had poor (47.32±.8%), moderate(64.67±6.63%), and good (84.11±5.75%) movement efficiency in single leg squat, double limb squat, and double limb squat with heel lift, respectively. Similarly, there is a positive and significant correlation between the total movement efficiency scores and New York test scores (p<0.05). Discussion and conclusion: Table tennis players had movement dysfunctions during functional movement patterns. There were correlations between functional movement errors and postural abnormalities. Based on the results it is recommended to coaches to concern about their athlete`s postures.